Region-wide assessment of the capacity for human nutrition training in West Africa: current situation, challenges, and way forward - Roger Sodjinou; Nadia Fanou; Lucie Deart; Félicité Tchibindat; Shawn Baker; William Bosu; Fré Pepping; Hélène Delisle (Taylor & Francis Group, 2014)
Background: There is a dearth of information on existing nutrition training programs in West Africa. A preliminary step in the process of developing a comprehensive framework to strengthen human capacity for nutrition is to conduct an inventory of existing training programs. Objective: This study was conducted to provide baseline data on university-level nutrition training programs that exist in the 16 countries in West Africa. It also aimed to identify existing gaps in nutrition training and propose solutions to address them. Design: Participating institutions were identified based on information provided by in-country key informants, UNICEF offices or through internet searches. Data were collected through semi-structured interviews during on-site visits or through self-administered questionnaires. Simple descriptive and bivariate analyses were performed. Results: In total, 83 nutrition degree programs comprising 32 B.Sc. programs, 34 M.Sc. programs, and 17 Ph.D. programs were identified in the region. More than half of these programs were in Nigeria. Six countries (Cape Verde, Guinea-Bissau, Liberia, Mali, The Gambia, and Togo) offered no nutrition degree program. The programs in francophone countries were generally established more recently than those in anglophone countries (age: 3.5 years vs. 21.4 years). Programs were predominantly (78%) run by government-supported institutions. They did not provide a comprehensive coverage of all essential aspects of human nutrition. They were heavily oriented to food science (46%), with little emphasis on public health nutrition (24%) or overnutrition (2%). Annual student intakes per program in 2013 ranged from 3 to 262; 7 to 40; and 3 to 10, respectively, for bachelor's, master's, and doctoral programs while the number of graduates produced annually per country ranged from 6 to 271; 3 to 64; and 1 to 18, respectively. External collaboration only existed in 15% of the programs. In-service training programs on nutrition existed in less than half of the countries. The most important needs for improving the quality of existing training programs reported were teaching materials, equipment and infrastructures, funding, libraries and access to advanced technology resources. Conclusions: There are critical gaps in nutrition training in the West Africa region. The results of the present study underscore the urgent need to invest in nutrition training in West Africa. An expanded set of knowledge, skills, and competencies must be integrated into existing nutrition training curricula. Our study provides a basis for the development of a regional strategy to strengthen human capacity for nutrition across the region.